Efficacy and safety of percutaneous pulmonary artery subtotal occlusion and CTO intervention in chronic thromboembolic pulmonary hypertension. (14th October 2021) - Gerges, C; Friewald, R; Gerges, M; Shafran, I; Sadushi-Kolici, R; Skoro-Sajer, N; Moser, B; Taghavi, S; Klepetko, W; Lang, I M
Abstract: Background: Balloon pulmonary angioplasty (BPA) is an emerging percutaneous therapy for patients with inoperable chronic thromboembolic pulmonary hypertension (CTEPH), and patients with mean pulmonary artery pressure (mPAP) ≤30mmHg have an excellent survival. Common vascular lesion types are ring-like stenoses (type A), web lesions (type B), subtotal occlusions (type C), chronic total occlusions (CTO, type D) and tortuous lesions (type E). Occlusive lesions (i.e. subtotal occlusions and CTOs) are most challenging. While the CTO intervention the coronary arteries remains controversial, risk and benefit of pulmonary artery occlusive lesion intervention in CTEPH has not been studied yet. We evaluated the impact of percutaneous pulmonary artery subtotal occlusion and CTO intervention on BPA treatment response. Methods: 120 patients underwent 712 BPA procedures between April 2014 and October 2019. Clinical features and hemodynamics were assessed at baseline and 6–12 months after the last BPA session. Results: A total of 2542 lesions were targeted; 720 occlusions (28.3%; 352 CTOs and 368 subtotal occlusions) and 1822 non-occlusion lesions (71.7%). Complications occurred in 6.0% of all procedures (severe complications in 0.4% of all procedures). 45 patients completed BPA treatment after a median of 6 (4; 10) procedures per patient. In these patients, mPAP dropped from 40.1±10.8 to 25.6±5.1mmHg (p<0.001), without significant change in cardiac output (5.2±1.4 to 5.5±3.1L/min, p=0.409). In the overall cohort, success rate for recanalization of occlusions was 81% (subtotal occlusions (type C lesions): 98%; CTOs (type D lesions) 50%). Number of successfully treated lesions of any type (β −0.86 [−1.19; −0.53]; p<0.001), number of successfully treated occlusions (β −2.17 [−3.38; −0.97]; p=0.001) and number of successfully treated non-occlusion lesions (β −0.81 [−1.25; −0.37]; p<0.001) emerged as predictors of relative change in mPAP. The impact on relative change in mPAP was higher for CTOs (β −5.88 [−10.49; −1.26]; p=0.014) than for subtotal occlusions (β −2.51 [−4.18; −0.83]; p=0.004). Conclusions: The number of successfully treated vascular lesions predicts treatment response to BPA. The number of successfully recanalized occlusions (particularly CTOs) appears to have the strongest impact on change in mPAP, highlighting the importance of advanced BPA technique. Funding Acknowledgement: Type of funding sources: None.